Super Built-Up Area: Examining Its Role in Real Estate Development and Urban Planning Strategies - Gourav Kumar Sharma (International Journal of Urban Design and Development, 2024)
The concept of Super Built-Up Area (SBA) has become pivotal in contemporary real estate development and urban planning strategies. Defined as the total area encompassing the built-up area of an apartment along with common areas like corridors, staircases, and amenities shared among residents, SBA influences both the economic viability of real estate projects and the spatial dynamics of urban landscapes. This study investigates the multifaceted role of SBA in shaping urban development. Through a comprehensive review of literature and analysis of case studies, the study examines how SBA calculations impact property pricing, consumer perceptions, and regulatory compliance in different urban contexts. Furthermore, it explores the implications of SBA on urban sprawl, infrastructure provisioning, and sustainable development goals. Key findings highlight the significant influence of SBA on housing affordability and urban density patterns. By delving into regulatory frameworks and market practices governing SBA calculations, the study uncovers variations in interpretation and implementation across regions, shedding light on challenges and opportunities for urban planners and policymakers. understanding the nuances of SBA is crucial for fostering equitable and sustainable urban growth. This research contributes to the discourse on effective urban planning strategies by elucidating the interplay between SBA, real estate dynamics, and urban development goals. Furthermore, it examines the correlation between SBA calculations and the effective utilization of urban spaces, highlighting potential discrepancies between reported and actual usable spaces. The analysis extends to the implications of SBA on urban planning policies, advocating for more transparent and standardized measures to enhance real estate market efficiency and urban livability
Keywords: Density Regulation; Land Utilization; Real Estate Development; Super Built-Up Area (SBA); urban planning